The Effect of Mgo Nano Filler Mixture On The Visual Aspects of Treeing Breakdown in Ldpe Based Composite - Rudi Kurnianto (Suara Teknik : Jurnal Ilmiah, 2010)
0px; "> This paper deals with a nano-composite of magnesium oxide (MgO) added toa low-density polyethylene (LDPE) which was subjected to an electrical treeingbreakdown investigation. When voltage application was set exactly at the inceptionlevel, even the tree had bridged the specimen the breakdown was not alwaysimmediately to occur. There would be so-called time-lag between “bridging” and“final breakdown”. The LDPE with MgO excelled to suppress the increase of treeparameters than that of LDPE without MgO. It is considered that the polymer nanocomposite is more resistive against partial discharge and then electrical treeing thantheir base material.Keywords : Nano, composite, MgO filler, LDPE, Electrical Treeing, Inception,Breakdown, Internal Flashover, Time-lag